The role of zinc in the prevention and treatment of nonalcoholic fatty liver disease - Mary Barbara (Metabolism Open, 2021)
The zinc element is an essential nutrient for human health. Zinc is involved in the glucose, lipid, and protein metabolism and antioxidant processes in biological pathways. Zinc deficiency can lead to several chronic liver diseases. Nonalcoholic fatty liver disease (NAFLD) is one of the most common liver diseases where zinc deficiency plays a critical role in pathogenesis. Human and animal studies showed that both NAFLD risk factors (i.e., insulin resistance, diabetes mellitus, dyslipidemia, obesity, hypertension) and NAFLD itself are associated with decreased blood levels of zinc. Additionally, endoplasmic reticulum stress and inflammation due to unfolded protein response, inadequate dietary zinc intake, and decreased zinc absorption from the gastrointestinal tract can result in zinc deficiency leading to NAFLD. Herein, we reviewed the mechanistic links between zinc deficiency and NAFLD development and the role of zinc in the prevention and treatment of NAFLD.